Terapi Non Farmakologi untuk Pasien Hipertensi - Novitayanti, Eka; Bakar, Abu; Efendi, Ferry (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to find out non-pharmacological measures to reduce blood pressure that can be carried out in the emergency room. The method used is a systematic review using the keywords Disinfectant Stethoscope via Scopus, Sage, Pubmed, and ScienceDirect. Inclusion criteria: full text (abstract, introduction, methods, results, discussion, and conclusions). The research results showed that from analyzing nine articles of non-pharmacological measures for hypertensive patients, namely Buteyko breathing, Bee-Humming Breathing Exercise, Phramari Pranayama, Aerobics, green tea extract (GT) and endurance training (RT), Inspiratory Muscle Strength Training, Aerobic exercise and stretching. In conclusion, Buteyko and bhramari pranayama are non-pharmacological measures that do not require much time. According to the author, they can be applied in the emergency room. Keywords: Hypertension, non-pharmacological therapy